Anti-discriminatory Practice in Mental Health Care for Older People. - Tribe, Rachel (Jessica Kingsley Publishers, 2017)
This book provides mental health students and practitioners with the key knowledge to carry out anti-discriminatory practice while working with older people from minority groups. With contributions from experts in the fields of mental health and care for older people, it looks at issues for practice, such as access to services for minority groups. Exploring the key issues around anti-discriminatory practice for professionals working in mental health services, this book looks at ways to improve the health and social care of older people from minority and excluded communities. The chapters explore the issues involved in working with individuals from a range of minority groups, such as LGBT people, people with learning disabilities, people from black and minority ethnic communities, homeless people and people with dementia. The chapters cover important theory and research into discrimination, ageing and identity. Contributions from experts in the fields of mental health and working with minority groups provide practical insights into developing anti-discriminatory practice. There is also practical advice on culturally appropriate support for carers, cultural competency in end of life care, working with interpreters, and celebrating diversity, accompanied by supporting practical resources. This comprehensive book will provide mental health practitioners and students with an essential understanding of anti-discriminatory practice.
Chapter 10. Understanding the Lives of Older Gypsies and Travellers and the Impact of Inequality on their Mental Health -- Siobhan Spencer and Pauline LaneChapter 11. Social Exclusion and Anti-discriminatory Practice: The Case of Older Homeless People -- Peter Cockersell; Part III -- Additional Information and Practical Guidance to Support Positive Practice; Chapter 12. The Rough Guide to Working with Interpreters in Mental Health -- Rachel Tribe and Pauline Lane; Chapter 13. Ageing, Food and Malnutrition -- Pauline Lane and Rachel Tribe; Contributors; Endnotes; Index; Blank Page.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Older people -- Mental health services; Mental health services; Minorities; Older people; Cultural competence; Mental Health Services; Ageism -- prevention & control; Minority Groups; Cultural Competency; Aged; United Kingdom; Aged, 80 and over; Personnes âgées -- Services de santé mentale; Services de santé mentale; Minorités.; Personnes âgées.; Compétence culturelle; minorities; elderly; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Older people; Minorities; Mental health services; Older people -- Mental health services